HEAVY METAL CONTENT IN WATER AND SEDIMENT IN THE SAIL RIVER PEKANBARU - Rina D'rita Sibagariang; Budijono Budijono (Berkala Perikanan Terubuk, 2021)
The Sail River is one of the largest tributaries of the Siak river in the city of Pekanbaru, which is located around a residential area. This study aims to determine the content of heavy metals (Cd, Fe, Cr, Cu) in water and sediments in the Sail River. The study was conducted in December 2017 - January 2018 using the survey method. The samples obtained were taken and analyzed at the Laboratory of Marine Chemistry at the Faculty of Fisheries and Marine Universitas Riau using Atomic Absorption Spectrophotometry (AAS). The heavy metal content in water for Cd is equal to the quality standard threshold; Fe, Cr, and Cu in water in the Sail river exceeds the water quality standard threshold in PP No. 82 of 2001. While the heavy metal content in the sediment for Cd, Fe, Cr, and Cu are still below the  CBSQG 2003 quality standard limits and ANZECC / ARMCANZ 2013 (revised).